Comparing General versus Spinal Anesthesia for Cesarean Section in a Severely Pre-eclamptic Parturients - Omer Abdalbagi Mohamed Elawad; Omayma Hassan Elamin; Areeg Izzeldin Ahmed Yousif; Gamal Abdalla Mohamed Ejaimi (Sudan Journal of Medical Sciences)
Background: Preeclampsia poses a high challenge during anesthesia. Both spinal anesthesia (SA) and general anesthesia (GA) are commonly used for the operative management of severe preeclampsia. The study aimed to assess feto-maternal outcomes among severely preeclamptic parturients scheduled for emergency cesarean section (C/S) delivery under GA or SA. Methods: A total of 80 parturients were enrolled into two equal groups, one group received SA and the other GA. Vital parameters were recorded before starting and during the procedure. The Chi-square test was used for analysis. A P-value of ≤0.05 was considered significant. Results: Both groups were similar in age, weight, parity, gestational age, and duration of surgery. An intraoperative need for vasopressors was higher in anesthesia (P-value 0.013). Significant intraoperative decreases in blood pressure were observed in SA. The rate of intensive care unit (ICU) admission was higher in GA (11 vs 4 patients, P-value 0.0463). Conclusion: Assuming no contraindication, SA is the first choice for cesarean section delivery in a severely preeclamptic parturient.